THE ROLE OF PODCASTS AND AUDIOBOOKS IN LANGUAGE EDUCATION (Scientific journal of the Fergana State University, 2024)
This study explores the role of podcasts and audiobooks in language education, emphasizing their impact on listening and speaking skills, vocabulary acquisition, and overall language proficiency. By employing a mixed methodology involving 100 language learners, the research utilizes quantitative assessments and qualitative interviews to evaluate the effectiveness of these digital resources. The findings demonstrate significant improvements in listening comprehension, speaking abilities, and vocabulary retention among participants who utilized podcasts and audiobooks. Additionally, students reported increased motivation and cultural awareness, despite facing challenges in understanding various accents. The study underscores the educational benefits of integrating podcasts and audiobooks into language education, highlighting the need for developing individual strategies to optimize their use. Future research should focus on identifying best practices in utilizing these tools to enhance language learning outcomes.